1994
DOI: 10.1007/bf01559535
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional reduction in non-supersymmetric theories

Abstract: It is shown that regularisation by dimensional reduction is a viable alternative to dimensional regularisation in non-supersymmetric theories.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(128 citation statements)
references
References 13 publications
5
123
0
Order By: Relevance
“…The DRED scheme is primarily used as a supersymmetric regulator and is quite cumbersome for non-supersymmetric calculations. It is, however, closely related to the FDH scheme and has been demonstrated [8,9,23,24] The calculation of the V boson decay rate provides another instance of the equivalence the CDR and DRED schemes at the four-loop level [23]. The ability to obtain the correct result using the DRED scheme required a delicate balance of the many extra couplings and their renormalization effects upon one another.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The DRED scheme is primarily used as a supersymmetric regulator and is quite cumbersome for non-supersymmetric calculations. It is, however, closely related to the FDH scheme and has been demonstrated [8,9,23,24] The calculation of the V boson decay rate provides another instance of the equivalence the CDR and DRED schemes at the four-loop level [23]. The ability to obtain the correct result using the DRED scheme required a delicate balance of the many extra couplings and their renormalization effects upon one another.…”
Section: Discussionmentioning
confidence: 99%
“…Because the effects of external evanescent states can be removed (or indeed never seen) by imposing a four-dimensionality restriction, and because the effects of internal evanescent states therefore contribute at order ε at one loop, it appears that one can simply ignore the distinction between gauge and evanescent terms. In contrast, because the DRED scheme must deal with external evanescent terms from the beginning, its advocates were forced to develop a successful renormalization program [8,9]. Extensive testing [8,9,23,24] has shown that this program works to at least the fourth order and that it handles the effects of both internal and external evanescent contributions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations